A Rapid Assessment Approach for Skin Stratum‐Targeted Drug Delivery Systems Using Mass Spectrometry Imaging and Spatial Clustering - Ravit Yakobi Arancibia; Einav Bentov‐Arava; Anna Morshin; Jhonathan Elia; Hiba Natsheh; Yael Levi‐Kalisman; Rotem Ushki; Anna Elia; Elka Touitou; Katherine Margulis (Small Science)
A novel mass spectrometry imaging (MSI)‐based concept that enables rapid visualization and evaluation of active pharmaceutical ingredient (API) distribution across skin layers following dermal delivery is presented. This approach integrates desorption electrospray ionization MSI with a newly developed automated computational tool (access provided) that efficiently processes MSI data, isolates skin tissue signals from background interference, and segments the tissue into precise layers. The tool facilitates detailed and rapid assessment of API localization within skin strata in under 10 min per skin specimen. To validate this method, three nanoscale dermal drug delivery systems (DDSs) for the antifungal terbinafine that target distinct skin strata—ethosomes, transethosomes, and microemulsion—are designed and characterized. API permeation in human and porcine skin is evaluated using both manual and automated workflows. The integrated approach demonstrates superior accuracy in skin distribution analysis, a substantial reduction in processing time, and improved efficiency in signal‐tissue overlay. Comparative analysis of the DDSs reveals marked differences in drug permeation depth and localization, with transethosomes showing the highest potential for deeper dermal delivery. This method not only provides a powerful tool for DDS evaluation but also enables detailed kinetic studies, offering insights into drug permeation dynamics.